2004
DOI: 10.1007/s00228-003-0708-x
|View full text |Cite
|
Sign up to set email alerts
|

Congruence on medication between patients and physicians involved in patient course

Abstract: Congruence between sources of information on medication throughout patient courses cannot be obtained with separate medication charts. Discrepancies among patient, general practitioner and hospital give rise to a definitive risk of serious untoward effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 25 publications
1
21
0
Order By: Relevance
“…These discrepancies on admission may result in inappropriate medication therapy during the hospital stay, which often carries over to discharge. Foss et al [8]. Conducted a study in Denmark which demonstrated that 48% of all drugs had a discrepancy when medication lists were compared between the hospital and patient immediately following discharge.…”
Section: Discrepanciesmentioning
confidence: 99%
“…These discrepancies on admission may result in inappropriate medication therapy during the hospital stay, which often carries over to discharge. Foss et al [8]. Conducted a study in Denmark which demonstrated that 48% of all drugs had a discrepancy when medication lists were compared between the hospital and patient immediately following discharge.…”
Section: Discrepanciesmentioning
confidence: 99%
“…Patients are often the primary source of providing their own medication status at the time of hospitalisation. Due to the risk of recall bias in patients, it is often necessary to supplement their information with that of others such as their general practitioner (GP), in-home care provider or pharmacy [1,5,6]. However, even given supplementary information, it has proven difficult to uncover patients' actual medication status upon hospitalisation, as there can be discrepancies between various medication lists due to lack of updating, among other reasons [1,2,7].…”
Section: Introductionmentioning
confidence: 98%
“…However, even given supplementary information, it has proven difficult to uncover patients' actual medication status upon hospitalisation, as there can be discrepancies between various medication lists due to lack of updating, among other reasons [1,2,7]. An incomplete medication history promotes the risk of medication error and misinterpretation of symptoms [1,2,6,[8][9][10]. Several methods to improve medication history have been tried in Denmark and elsewhere, such as questionnaires, structured medication interviews, a review of the medicines patients have brought with them, a prescription list from the GP and prescription data from the pharmacy [5,6,8,9,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations